In situ exsolution of Ag from AgBiS2 nanocrystal anode boosting high-performance potassium-ion batteries. Issue 30 (21st July 2020) - Ren, Xiaoru; Yu, Dongxu; Yuan, Long; Bai, Yaocai; Huang, Keke; Liu, Jinghai; Feng, Shouhua
Abstract : In situ Ag exsolution from AgBiS2 nanocrystals as an intermediate charge transmitter assists cycling for K + intercalation in anode reactions. Abstract : The irreversible formation of a solid electrolyte interface (SEI) film on semimetal/semiconductors impedes the electrochemical migration of K + in potassium-ion batteries due to the inevitable volume expansion of the anode materials. Herein, we report the in situ exsolution of Ag in metastable nanostructured AgBiS2 to spontaneously assist cycling for K + intercalation. The in situ XRD and ex situ HRTEM techniques revealed unique phase transitions during the uptake of K + on account of the mixed ion storage mechanism. During the initial reduction process, AgBiS2 underwent K + /AgBiS2 displacement, K + /BiS2 conversion, and K + /Bi alloying reaction. The exsolution of Ag was electrochemically reduced in the process of K + insertion and remained as an intermediate charge transmitter to sustain a high reversible capacity of 420 mA h g −1 at 0.5 A g −1, superior rate performance of 210 mA h g −1 at 5 A g −1 and long-term (over 300) cycle stability. This work presents a strategy to resolve the issues of single-element anodes in metal-ion batteries.